Ant composition and competitive interactions with Wasmannia auropunctata in Tropical Dry Forest fragments - ACHURY, RAFAEL; CHACÓN DE ULLOA, PATRICIA; ARCILA, ÁNGELA MARÍA (Revista Colombiana de Entomología, 2008)
Disturbance increases the probability of dominance by the little fire ant Wasmannia auropunctata (Formicidae: Myrmicinae), an indicator species of low diversity ant communities in Tropical Dry Forest fragments of the Cauca River Valley (Colombia). In order to study interactions of interspecific competition involving this species, we conducted experiments with soil-surface tuna-baits at four localities: Alejandría, El Medio, El Vínculo and San Julián. Three biotopes were distinguished at each locality: forest interior, forest margin and their surrounding matrices (sugar cane or pasture). Based on information obtained from the composition of ants at the baits, competition ability indices were calculated. Attraction to the baits was 91%, for a total of 66 species in 30 genera. Species composition was mainly influenced by locality conditions. The myrmicines Pheidole, Solenopsis and Crematogaster had the greatest interaction with W. auropunctata and partitioning of the baits was mostly influenced by biotope. Bait use by other species was determined by the abundance of W. auropunctata; if the bait had more than a mean of 500 workers, the resource was not shared. W. auropunctata emerged as the dominant species in the upper Cauca River watershed and this was mainly accomplished by exploitation competition, allowing the ants to rapidly take advantage of resources by recruiting a large number of workers.